Resilience and adolescence-transition in youth with developmental disabilities and their families: a scoping review - Zukerman, Naomi; Bottone, Emily; Low, Maya; Ogourtsova, Tatiana (Frontiers in Rehabilitation Sciences, 2024)
Background: Children with neurodevelopmental disabilities (NDDs, e.g., cerebral palsy) and their caregivers face lifelong and impactful challenges, particularly during life-transition periods such as adolescence. One's resilience emerges as an essential ability to navigate this vulnerable phase. Resilience is a complex concept that embeds multiple factors on various levels. Little is known about what resilience factors are pivotal in youth with NDDs and their families as they transition into adolescence and how these are addressed as part of existing targeted interventions. Objectives: This review explored the concept of resilience in youth with NDDs and their families. Specific aims included describing salient resilience factors in adolescents with NDDs and their families and to describe how resilience is addressed as part of targeted interventions. Methods: Using the Arskey and O'Malley framework, six steps were undertaken, including a comprehensive literature search (n=5 databases), transparent study selection, detailed data extraction with a coding scheme (n=46 factors), results' collating with numerical and inductive content analysis, and consultation with three key stakeholders.The study screened 1,191 publications, selecting fifty-eight (n=58; n=52 observational and n=6 intervention) studies. Findings revealed that resilience in this context is closely linked to more than forty factors across four levels (individual; family; school/peers; and community). Pivotal factors include social and emotional competence, optimism, and family/peer relationships. While existing interventions targeting resilience show promising results, few programs are available and generalizable to different NDDs. Stakeholders highlighted the importance of addressing resilience factors that are not targeted in existing interventions: caregivers' self-efficacy and self-esteem, as well as youth's and caregiver's confidence. Preferences for and advantages of online delivery for support programs and individual/group features also emerged.The review emphasizes the need for a holistic approach to support youth with NDDs and their families during adolescence transition. To enhance their resilience, recognizing caregivers' roles, customizing interventions, and exploring new implementation formats are avenues that align with the current evidence and opportunities for practical development in this field.